Innovative management in the public service : towards service delivery imperatives - Shipalana, M. L. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
It is broadly conceded that management function as an element of innovative management, is viewed as playing a vital role in the management of systems and processes while, leadership focuses on strategic direction for service delivery imperatives in public service institution, particularly in the public health institutions for the provision of quality health care services. For modern and highly technological resultsdriven public management, innovation remains a critical element of management functions and needs to be taken seriously in order to be responsive to household needs in the 21st century and beyond. Innovative management development in respect of the public sector would be seen as contributory factor to address the underlying challenges regarding service delivery, specifically developing countries in Africa. However, it is observed that public service institutions are usually branded by ineffective innovative management strategies and approaches that affect the provision of quality goods and services. The innovative management challenges are seen as impediments towards effective and efficient application of innovation initiatives, particularly on aspects such as policies, procedures and systems that aim at service delivery improvement. This paper sought to analyse innovative management challenges and highlights strategies as well as approaches to enhance delivery of service in public service institutions. Qualitative approach with data collection methods was used, which included semi-structured and focus group interviews as well as analysis of official documents. In the course of analysing data, the findings revealed that public service institutions are characterised with ineffective innovative management due to poor diffusion of innovations, rigid rules and regulations and a culture of resistance to change. This article further suggests collaborative innovation and techniques on management of innovations as mechanisms to address innovative management challenges for service delivery enhancement in the public service.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Innovation; Innovative management; Public service; Public health institutions; Service delivery imperatives; Health services administrators